2018
DOI: 10.1177/0300060518766982
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of oral nutritional supplementation supports continued growth in nutritionally at-risk children with picky eating behaviour: A post-intervention, observational follow-up study

Abstract: ObjectivesTo evaluate the 120-day post-intervention growth trajectory of picky-eating children aged 2 to 6 years who previously completed a 90-day, randomized, controlled trial of oral nutritional supplementation (ONS) plus dietary counselling (DC) (SDC, n = 98) compared with DC alone (n = 105).MethodsA total of 203 children were included. Children were free to consume ONS during follow-up. Information on ONS consumption was collected. Weight-for-age percentile (WAP) and height-for-age percentile (HAP) were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Eleven studies met the inclusion criteria ( Figure 1 ). Of these, seven were considered to be of “high” quality [ 23 , 47 , 48 , 49 , 50 , 51 , 52 ] and two each “moderate” [ 53 , 54 ] and “low” [ 55 , 56 ] quality ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies met the inclusion criteria ( Figure 1 ). Of these, seven were considered to be of “high” quality [ 23 , 47 , 48 , 49 , 50 , 51 , 52 ] and two each “moderate” [ 53 , 54 ] and “low” [ 55 , 56 ] quality ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet it could also negatively effects the nutritional status of a child. On the other because it decreases mother caring-time for a child (Ghosh, Kishore, Shaikh, Satyavrat, Kumar, & Shah, et al, 2018b) found that mother's malnourished children are almost working women, however Karlsson, Kim, Sarwal, et al (2021) did not find any evidence on the relationship between children's nutritional status and mothers' employment.…”
Section: Educationmentioning
confidence: 89%
“…It is especially important to note that the odds ratios are not comparable in magnitude across study designs-for example, one study finding that overweight kids are five times as likely to be picky does not mean that picky kids are five times as likely to be over or under weight. Even in studies that found a relationship between picky eating and overweight like the article that made by (Taylor, Steer, Hays, & Emmett, 2018) Also, most studies did not clearly report possible effect modifiers e.g., types of foods offered to the child, parenting styles, oral nutritional supplementation, growth (Ghosh et al, 2018), nutritional status, development, physical activity, and health (Chao, 2018), sosioeconomy (Galloway et al, 2018) parent weight status) that could affect the relationship between eating behaviors and weight status. Other limitations that may affect the cumulative evidence in this systematic review include publication bias and the risk of selective reporting within studies.…”
Section: Discussionmentioning
confidence: 99%
“…Picky eating so far has not been understood the effect on body weight and height in children, where the problem can be at risk for nutritional status in children (Ghosh et al, 2018). In Southeast Asia there is a prevalence of overweight 4.2% from 19.9 million in Asia and 15.1% of 86.5 million in Asia experiencing stunting (United Nations Children's Fund, Organization, & Bank, 2017).…”
Section: Introductionmentioning
confidence: 99%